So You Want to Start an Institutional Biosafety Committee. (September 2019) - Schniederberend, Maren; Fontes, Benjamin; Jeffrey, Rachel
Introduction: The number of institutions engaging in research with potentially biohazardous materials has increased, indicating a need for newly formed Institutional Biosafety Committees (IBCs) in the United States and for similar biorisk management committees located outside the United States. Our institution identified the need for an IBC due to the growth of pertinent activities on campus. Objectives: This article shares our experiences creating a new IBC at our institution from September 2017 to April 2019. Our lessons learned and approaches to the challenges faced may be helpful to others finding themselves with similar needs. Methods: In this case study, we outline IBC membership, documents, relationships with federal agencies and within the institution, creation of registration forms, and the review process. Along with our account, we have included links to helpful resources from federal agencies. Results: At the time of the submission of this article, we have established our IBC and reviewed two registrations. Conclusion: This case report demonstrates the successful creation of an IBC that works for our current institutional needs.